Analysis of Incentive Policy Implementation For Regional Health Workers Handling Covid-19 In Regional Financial Management In South Tangerang City In 2021 - Rahman, Desvanty; Bawono Adisasmito, Wiku Bakti (Green Publisher Indonesia, 2022)
There are differences in the results of the implementation of Innakesda policy in the regions carried out by the Regional Government. There are local governments that have succeeded in implementing this policy and there are also local governments that have not succeeded in doing so. The analysis was conducted to see the success of Innakesda policy implementation from the dimensions of actors, content, context and processes in local financial management. The location of the research was carried out in one of the areas that successfully implemented the Innakesda policy, namely South Tangerang City. The conclusion of the study provides an illustration that there are situational context factors in handling the pandemic that rely on the role of health workers as the frontline, structural factors on the principle of decentralization of local government administration and cultural factors. Innakesda policy content in the harmonization of regulations and various efforts to evaluate policy implementation is also carried out by the central government and the results are used as input in making improvements to policy content to accelerate the realization of Innakesda in the South Tangerang City. The Political Will of the Mayor of South Tangerang is a key role in Innakesda policy implementation process in managing regional finances from the planning and budgeting stages through integration and coordination of refocusing and budget reallocation while maintaining conformity/alignment of achieving RPJMD targets and staying focused on the COVID-19 handling program. In the implementation and administration stages, the South Tangerang Government pays attention to the principles of order and compliance in regional financial management supported by a smart reporting system using technology for the Planning, Budgeting and Reporting Management Information System (SIMRAL).